ANALISIS PENILAIAN KINERJA RUMAH SAKIT UMUM DAERAH KOTA DUMAI SEBAGAI BADAN LAYANAN UMUM DAERAH - Wilda, Wilda; Sari, Ria Nelly; Rasuli, M. (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This research aims to analyze the performance measurement of RSUDKota Dumai defined as Regional Public Service Agency (BLUD). Performance is one of important thing that have to evaluate at public hospital to obtain the objective and increase quality of health services. In this research , we investigate how RSUD Kota Dumai measure the performance. This research uses qualitative method with case study design. The sampling conducted in this research are purposive sampling. Methode of data collection obtained through in dept interview, observation and dokumentation. The interview are conducted with all director of RSUD Kota Dumai. The result showed RSUD Kota Dumai evaluate performance under a combination of financial and non financial indicator. We found the method of financial performace measurement used budgetting analysis and non financial performance measurement used : (1) The achievement of employee, (2) Achievement of service performance indicator, (3) Survey of patient satisfaction, (4) Survey of employee satisfaction, (5) Performance Audit.In Conclusion this paper offer Balanced Scorecard to evaluating the performance of hospital activity. Balanced Scoecard Indicator have proved effective for measuring and improving hospital performance in four distinct factors : financial result, customer satisfaction, the internal business process, learning and growth effectiveness. We suggest RSUD Kota Dumai can adopt Balanced Scorecard. However Balanced Scorcard will help public hospital to measure their performance more comprehensive and accurate.